Parental resilience: A neglected construct in resilience research. (7th January 2015) - Gavidia‐Payne, Susana; Denny, Bianca; Davis, Kate; Francis, Andrew; Jackson, Merv
Abstract The substantial focus of resilience research on childhood well‐being has resulted in limited knowledge regarding other aspects of resilience in families, such as that of parents. Informed by literature in childhood and family resilience, in this review, we progress conceptual understanding by focusing on parental resilience. The definition of parental resilience, as the capacity of parents to deliver a competent and quality level of parenting to children despite the presence of risk factors, is offered here as a worthwhile framework through which to explore variables thought to contribute to resilience among parents. A conceptual model is proposed whereby parental psychological well‐being and self‐efficacy, family functioning, and social connectedness are specifically addressed, with each posited as playing an important role in parents' ability to deliver high‐quality parenting. In addition to these factors, how parents accommodate adversity and find meaning in their everyday lives within their families is hypothesised to be an important process in understanding parental resilience.